Proposing an Appropriate International Jurisdictional Rule for Preventing Libel Tourism: A Comparative Study of Iranian and English Law - Sayyed Hossein Safaei Moafi; Reza Maghsoudi; Reza Daryaee (پژوهشنامه حقوق تطبیقی)
Libel tourism refers to a situation in which, despite the presence of multiple competent courts, a claimant can file a defamation lawsuit in a country with favorable laws, even when there is minimal connection between the jurisdiction and the claim. This phenomenon raises significant concerns regarding the violation of individual rights, media integrity, and freedom of expression. Consequently, legal systems should take measures to curb the proliferation of this issue by establishing appropriate jurisdictional rules that ensure a sufficient connection between the claim and the court. What type of jurisdictional rule is appropriate for defamation lawsuits? This research employs a descriptive-analytical method, utilizing a comparative approach and library sources. The primary objective of this study is to propose a favorable jurisdictional rule by examining the international jurisdictional regulations of the Iranian and English legal systems, with the aim of preventing the proliferation of libel tourism. The findings of this article indicate that the rules governing Iranian international jurisdiction create opportunities for abuse by defamation claimants, potentially leading to the proliferation of libel tourism in the country. Therefore, it is essential to modify these jurisdictional rules. In contrast, the English legal system has managed to mitigate the emergence of libel tourism to some extent by granting authority to exercise jurisdiction in defamation lawsuits. The results of this research indicate that the jurisdictional rule granting the court the authority to determine its jurisdiction based on the specific issues of each case, and to identify the most suitable venue for hearing the case, is the most effective rule.